3p26.3 terminal deletions: a challenge for prenatal genetic counseling. (30th January 2017) - Bertini, Veronica; Azzarà, Alessia; Toschi, Benedetta; Gana, Simone; Valetto, Angelo
Abstract : WHAT'S ALREADY KNOWN ABOUT THIS TOPIC? Several cases of 3p terminal deletion have been reported, but those with hemizygous deletions of 3p26.3, harboring only the CHL1 gene, are quite rare. The associated phenotype is quite variable, and the clinical meaning of this imbalance has still to be fully elucidated. WHAT DOES THIS STUDY ADD? For a prenatal genetic counseling, we have reviewed the data present in the literature and public databases. It emerges that this 3p26.3 deletion, harboring only the CHL1 gene, is not sufficient per se to cause a pathological phenotype, and is a prototopic example of Variant Of Unknown Significance. The finding of this variant in the fetus does not provide any significant information about the phenotypic outcome.